Why not de-intensification for uterine cervical cancer? - Naoya Murakami (2022)
Objective: The majority of uterine cervical cancer is known to be related to human papillomavirus (HPV), and HPV-related tumors are known to be radio-sensitive. In the management of HPV-related oropharyngeal cancer, de-intensification of treatment has been attempted; however, no such attempt is performed in the management of cervical cancer. The aim of this study was to identify a group of patients who can safely be treated by de-escalated treatment intensity. Methods: From the Asian international multi-institutional retrospective study involving 13 Japanese, one Thailand, and one Korean institutions based on 469 patients, squamous cell carcinoma (Scc), tumor reduction ratio ≥29%, tumor size before brachytherapy ≤4 cm, and total treatment time (TTT) <9 weeks were identified as factors having an influence on local control. Based on these findings, low-risk patients having these four factors were extracted, and treatment outcomes categorized in 10 Gy increment of CTVHR D90 were compared. Results: Among 469 patients, 162 patients (34.5%) met the criteria of low-risk group, and 63, 41, 43, and 15 patients were categorized in CTVHR D90 50–60 Gy, 60–70 Gy, 70–80 Gy, and >80 Gy, respectively. While 4-y progression-free survival ranged from 66 to 80%, 4-y local control was consistently over 90% in every dose group. Rectum and bladder D2cc and incidence of late adverse events decreased as CTVHR D90 decreased. Conclusions: The low-risk patients achieved favorable local control with CTVHR D90 <80 Gy. A personalized treatment strategy based on tumor response could also be adopted for cervical cancer.